Exposure to liquid detergent capsules: A study undertaken by the UK National Poisons Information Service - Williams, Hayley; Bateman, D. Nicholas; Thomas, Simon HL; Thompson, John P; Scott, Robert AH; Vale, J. Allister (Clinical toxicology (Philadelphia, Pa.), 2012)
Objective. To ascertain the reported toxicity of liquid detergent capsules. Methods. Between 1 March 2008 and 30 April 2009 the UK National Poisons Information Service collected prospectively 647 telephone enquiries relating to liquid detergent capsules. Results. The majority of enquiries (96.1%) concerned children of 5 years of age or less. Exposure to these products occurred mainly as a result of ingestion alone (n = 518; 80.1%), with eye contact alone (n = 61; 9.4%), and skin contact alone (n = 7; 1.1%) being less common; multiple routes of exposure were involved in 61 (9.4%) enquiries. Following ocular exposure, conjunctivitis with or without eye pain (n = 61), eye pain alone (n = 11) and keratitis (n = 4) developed; in one case the keratitis persisted for nine days, though recovery occurred in all cases as far as is known. The most common features reported following ingestion alone were nausea and vomiting (n = 143), followed by coughing (n = 21). Eleven children less than 2 years of age also developed drowsiness. A rash occurred in nine patients where ingestion was considered to be the route of exposure, probably due to topical contact with the capsule. Seven children aged 3 or less were exposed via the dermal route alone and developed rash (n = 4), irritation (n = 2), chemical burn (n = 2), and paresthesia (n = 1). Conclusions. Ocular exposure may lead to conjunctivitis and keratitis; recovery is to be expected in all cases within 7-10 days. Ingestion may also result in drowsiness. Greater consumer awareness is required to reduce injury from liquid detergent capsules, particularly that involving the eye. Parents have a vital role to play in ensuring that these products are stored safely at all times.